2008
DOI: 10.3141/2069-10
|View full text |Cite
|
Sign up to set email alerts
|

Traveler Information Delivery Mechanisms

Abstract: Advanced traveler information systems (ATISs) help individuals make informed travel decisions. Current ATIS applications encompass a variety of delivery mechanisms, including the Internet, telephone, television, radio, variable message signs, and in-vehicle navigation devices to support decisions about destinations, travel mode, departure time, routes, parking, and trip cancellation. It is important for researchers and practitioners to review the status of ATIS technologies and to understand travelers’ access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…Given the various characteristics of the competing ATIS applications, because of the greater accessibility and portability of radio, most of the articles concluded that the RTI is the most successful ATIS application to assist route diversion [8,[11][12][13][14]. However, the flow of new technologies to the developing countries is paving the way for other ATIS technology-based applications, such as the Internet and VMS.…”
Section: Multinomial Logit Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the various characteristics of the competing ATIS applications, because of the greater accessibility and portability of radio, most of the articles concluded that the RTI is the most successful ATIS application to assist route diversion [8,[11][12][13][14]. However, the flow of new technologies to the developing countries is paving the way for other ATIS technology-based applications, such as the Internet and VMS.…”
Section: Multinomial Logit Modelmentioning
confidence: 99%
“…Theme References (i) Propensity of acquiring traffic information Age * Older commuters have a higher propensity to acquire RTI advisories [1] * Younger commuters are more likely to acquire traffic information [14] Gender * Females are more likely to change their travel patterns [1] * Females are less likely to be influenced by traffic information [4] * Males desire more traffic information [6] Willingness-to-pay for en route dynamic traffic information is relatively high for male drivers on business trips [4] Commuters on longer trips desire traffic information [10,11,13,14] Commuters on work trips desire traffic information [10,11] (ii) Propensity of changing the routine travel plan or diversion to alternative routes…”
Section: Areamentioning
confidence: 99%
See 2 more Smart Citations
“…websites, public announcements, or mobile devices [4]. Zhang et al [8] illustrate the value of providing real time passenger information (RTPI) at this stage.…”
Section: Introductionmentioning
confidence: 99%